2004
DOI: 10.1038/sj.onc.1207855
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular pathology at crossroads to establish causation: molecular mechanisms of malignant transformation

Abstract: Epidemiology is a very reliable science for the identification of carcinogens. Epidemiological studies require that the effect, cancer in this case, has already occurred, when of course it would be more desirable to identify potential carcinogenic substances at an earlier stage before they have caused a large number of malignancies and thus become identifiable by epidemiological studies. In the past 30 years, molecular pathology (which includes chemistry, biochemistry, molecular biology, molecular virology, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 65 publications
0
6
1
Order By: Relevance
“…p53 signaling is believed to be disrupted in virtually all metastatic cancers (52)(53)(54)(55). In contrast to Madh4 and p21-Cip1/Waf1, we could not detect any obvious downregulation and p19-Arf expression levels were unchanged in the tumor tissue.…”
Section: Molecular Analysis Of Pancreatic Adenocarcinomascontrasting
confidence: 75%
“…p53 signaling is believed to be disrupted in virtually all metastatic cancers (52)(53)(54)(55). In contrast to Madh4 and p21-Cip1/Waf1, we could not detect any obvious downregulation and p19-Arf expression levels were unchanged in the tumor tissue.…”
Section: Molecular Analysis Of Pancreatic Adenocarcinomascontrasting
confidence: 75%
“…Although it was reported that overexpression of Acrogranin in a cancer cell line (SW-13) augmented the tumorigenicity in nude mice (17), this is the first study showing that Acrogranin endows tumorigenicity to phenotypically normal cells which originally did not form tumors in nude mice. Studies on in vitro-malignant transformation have revealed that, in order to transform primary human cells, the following four signals are necessary: 1) maintenance of telomere length by hTERT expression, 2) perturbation of p53 and RB by SV40LT expression or other methods, 3) perturbation of PP2A by SV40 ST expression or other methods, 4) constitutive RAS signaling by transfection of the oncogenic allele of RAS (18)(19)(20)(21). In general, signals from growth factors are transmitted through tyrosine kinase-type receptors to RAS (22).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the measurements of response in epidemiologic studies reflect late-stage end points of morbidity, mortality, body weight decrease, tumor development, and tissue pathology (Bocchetta and Carbone 2004; Maier et al 2004). Defining risk at a late stage in the disease process provides little opportunity to intervene and redirect the outcome.…”
Section: Exposure Assessment Methodsmentioning
confidence: 99%